Knowledge management in construction companies (Advances in Knowledge Representation, 2023)
The construction industry is knowledge intensive. This topic is extremely relevant in several countries, where a lot of knowledge is generated when executing construction projects and part of this is not retained by construction companies. The objective of this work is to identify how construction companies use the knowledge acquired when executing construction projects, and transform it into organizational knowledge, in order to obtain better results in future projects. For this, a literature review was carried out, through the reading and interpretation of selected documents, and a questionnaire was applied, which was sent to 150 engineers working in construction companies, obtaining 101 responses. The results of the questionnaire were analyzed and associated with the data collected in the literature review. It could be observed that knowledge management in the construction industry is a challenge, and that efficient knowledge management would allow construction companies to transfer knowledge between their various projects in order to obtain better results.